2015
DOI: 10.2109/jcersj2.123.955
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of CeO<sub>2</sub>-supported bimetallic Ni&ndash;Cu, Co&ndash;Cu, and Ni&ndash;Fe catalysts on steam reforming of ethanol

Abstract: The synergistic effects of CeO 2 -supported bimetallic NiCu, CoCu, and NiFe catalysts on the reduction properties, crystal structure, and catalytic performance during steam reforming of ethanol were investigated. Both metals in the bimetallic catalysts were reduced at lower temperatures than were the metals in the associated monometallic catalysts, and they formed alloy crystallites. It was confirmed from activity tests of the monometallic catalysts that Ni and Co were relatively active components and that Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
7
0
8
Order By: Relevance
“…We also demonstrated that the addition of relatively inactive Cu to Ni/CeO2 and Co/CeO2, each at metal loadings of 5 wt%, resulted in enhancement of the H2 yield and resistance to carbon deposition at 673 K 30) . In this study, we report the effects of the Ni : Cu ratio and metal loading on the reduction behavior of bimetallic Ni _ Cu catalysts supported using pure CeO2 and their catalytic performance for SRE.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We also demonstrated that the addition of relatively inactive Cu to Ni/CeO2 and Co/CeO2, each at metal loadings of 5 wt%, resulted in enhancement of the H2 yield and resistance to carbon deposition at 673 K 30) . In this study, we report the effects of the Ni : Cu ratio and metal loading on the reduction behavior of bimetallic Ni _ Cu catalysts supported using pure CeO2 and their catalytic performance for SRE.…”
Section: Introductionmentioning
confidence: 69%
“…Figure 7 shows the TG profiles of the catalysts employed for SRE at 673 K and 873 K for 9 h. The total quantities of the carbon deposits estimated from the weight losses are summarized in Table 1. The weight losses due to carbon combustion were classified into two groups: a small weight loss at 490-530 K and a relatively large weight loss at ≥ 600 K. As described previously 29), 30) , the former is related to carbon deposits chiefly on Cu, and the latter is attributed to fibrous carbon deposits on Ni. At a reaction temperature of 673 K, Ni10 produced a relatively large quantity of carbon, which was reduced by more than half by replacing only 2 wt% of the Ni with Cu (Ni8Cu2).…”
Section: C a T A L Y T I C P E R F O R M A N C E F O R S R E A N Dmentioning
confidence: 96%
“…In addition to the influence of Ni on the breakdown of C–C bonds, Ni has characteristics that favor methane reform, or methane consumption, as well as temperature increase. , The influence of these factors, Ni and temperature, on methane reforming was clearly observed in the regression model adjusted for the CH 4 flow, so that both Ni and the interaction between it and temperature favored CH 4 consumption (region F of Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, Ni favors a greater conversion of CH 4 and CO, 6 as it facilitates the breakdown of the C−C bond 7,8 and does not suffer CO poisoning. 6 However, in spite of these advantages, Ni favors the formation of coke, 9,10 and to avoid coke deactivation, some studies indicate the coparticipation of Cu in the presence of Ni as responsible for the decrease of coke and CH 4 . 8,9 Among the supports studied for the steam or oxidative reforming of ethanol, the support that presents high mobility of oxygen atoms and hydroxyls is CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation